2019
DOI: 10.1111/pbr.12707
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Striga hermonthica adaptive traits in an early‐maturing white maize inbred line containing resistance genes from Zea diploperennis

Abstract: Striga hermonthica can cause as high as 100% yield loss in maize depending on soil fertility level, type of genotype, severity of infestation and climatic conditions. Understanding the mode of inheritance of Striga resistance in maize is crucial for introgression of resistance genes into tropical germplasm and deployment of resistant varieties. This study examined the mode of inheritance of resistance to Striga in early‐maturing inbred line, TZdEI 352 containing resistance genes from Zea diploperennis. Six gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Different reports on gene action controlling Striga resistance and tolerance, grain yield, low N tolerance, and other traits of maize lines are available. Additive genetic effect was reported to be more important than nonadditive effect in modulating Striga resistance (Amegbor et al., 2017; Gethi & Smith, 2004), whereas nonadditive gene action played greater role in genetic control of Striga resistance trait (Akaogu et al., 2019; Kim, 1994). Also, dissimilar reports are available on the genetic effect controlling maize grain yield in low‐N environments.…”
Section: Introductionmentioning
confidence: 99%
“…Different reports on gene action controlling Striga resistance and tolerance, grain yield, low N tolerance, and other traits of maize lines are available. Additive genetic effect was reported to be more important than nonadditive effect in modulating Striga resistance (Amegbor et al., 2017; Gethi & Smith, 2004), whereas nonadditive gene action played greater role in genetic control of Striga resistance trait (Akaogu et al., 2019; Kim, 1994). Also, dissimilar reports are available on the genetic effect controlling maize grain yield in low‐N environments.…”
Section: Introductionmentioning
confidence: 99%
“…Its prominence has increased in SSA owing to its use as a cheap energy source in both human and livestock diets. The high insolation, cold night, and minimal occurrence of pest and diseases that characterize the savanna agroecology of SSA make it an ideal environment for maize production [1]. The early maturing maize varieties that are often available in July during the food deficit period, when other food reserves have been exhausted due to the extended hunger period, have helped to alleviate starvation in the savannas of SSA [2].…”
Section: Introductionmentioning
confidence: 99%
“…Striga parasitism is a limiting factor to maize ( Zea mays L.) cropping in the savannah zones of Sub‐Saharan Africa (SSA) which constitutes the maize belt of the sub‐region (Runo & Kuria, 2018). About 75% of cultivated land with maize in SSA is endemic to S. hermonthica (Akaogu et al., 2019). Maize yield losses under severe Striga infestation can be as high as 100% (Figure 1) and are economically estimated to $7 billion in the SSA alone (Spallek et al., 2013).…”
Section: Economic Impact Of Striga Infestation On Maize Production and Biology Of Striga Sppmentioning
confidence: 99%
“…In contrast, other studies reported that the impact of non‐additive genes is more important than the effect of additive genes in the control of the inheritance of host plant damage, while the effect of additive genes is more important in the control of the number of emerged Striga plants (Gethi & Smith, 2004; Badu‐Apraku et al., 2007; and Yallou et al., 2009). A recent study reported that the dominant effects surpass the additive effects for the number of emerged Striga plants and inheritance of Striga resistance in maize may be conditioned by non‐additive gene action (Akaogu et al., 2019). Additionally, the involvement of epistatic effects in the inheritance of Striga resistance aa in maize has been reported (Adetimirin et al., 2001; Akaogu et al., 2019).…”
Section: Genetics Resistance Mechanisms To Striga In Maizementioning
confidence: 99%
See 1 more Smart Citation